Pengaruh Faktor Keuangan dan Nonkeuangan terhadap Indikasi Manipulasi Laporan Keuangan (Studi Empiris pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2024) - Jessica Valencia Hutapea (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The potential losses caused by financial statement manipulation highlight the importance of early detection of such indications to prevent greater impacts on stakeholders. This study aims to analyze the effect of financial and non-financial factors on the indication of financial statement manipulation. The sample consists of 24 energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period, with a total of 96 observations. Hypothesis testing using logistic regression shows that financial statement manipulation is significantly influenced by financial stability and the frequency of CEO photo appearance. Meanwhile, political connections within the board of commissioners are found to reduce the indication of manipulation, reflecting stronger monitoring due to public scrutiny. In contrast, ineffective supervision, auditor turnover, and CEO tenure show no significant effect. Overall, this study contributes both theoretically and practically to understanding the role of financial and non-financial factors in supporting early detection of financial statement manipulation.